2017
DOI: 10.1007/s13187-017-1207-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Providing Web-Based Information to Breast Cancer Patients Prior to a Surgical Consult

Abstract: Patients facing decisions for breast cancer surgery commonly search the internet. Directing patients to high-quality websites prior to the surgeon consultation may be one way of supporting patients' informational needs. The objective was to test an approach for delivering web-based information to breast cancer patients. The implementation strategy was developed using the Replicating Effective Programs framework. Pilot testing measured the proportion that accepted the web-based information. A pre-consultation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“… 259 +++ pediatric asthma clinic USA Asthma Patient education Demographic data, Patient awareness Patient-provider communication, Appointment intake information 15 19 Tucholka, J. L. et al [ 39 ] 2018 J Am Coll Surg Online and offline sources of information and support To assess the acceptability of a new strategy of pre-consultation prevention summaries and reminders in general practice. 377 patients +++ Breast cancer clinic USA Breast cancer Patient education Demographic data, Patient awareness Illness perceptions, Medication and treatment adherence 16 20 Aboumatar, H. J et al [ 66 ] 2013 J Gen Intern Med Online and offline sources of information and support Combining patient-oncologist intervention to improve communication in advanced cancer 41 primary care physicians and 275 of their patients +++ Primary care clinic USA Hypertension Patient education Demographic data, Patient awareness Appointment intake information 18 21 Albada, A. et al [ 29 ] 2015 Patient Educ Couns Electronic pre-office visit checklist To help reduce waiting times and duplication of work, improve patient pathways and decrease wasted visits 197 patients + Breast cancer clinic Norway Breast cancer Decision aid tools, Pre-assessment tools, Reminders Demographic data, Medical history, Family history, Reason for referral, Symptoms, Medication Patient-provider communication, Perceived involvement in care, Adherence to visit scheduling, Visit length 18 22 Bruce, J. et al [ 60 ] 2018 J Cancer Educ Online and offline sources of information and support To evaluate teen feedback on an asthma question intervention designed to motivate teens to be more engaged during visits and …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 259 +++ pediatric asthma clinic USA Asthma Patient education Demographic data, Patient awareness Patient-provider communication, Appointment intake information 15 19 Tucholka, J. L. et al [ 39 ] 2018 J Am Coll Surg Online and offline sources of information and support To assess the acceptability of a new strategy of pre-consultation prevention summaries and reminders in general practice. 377 patients +++ Breast cancer clinic USA Breast cancer Patient education Demographic data, Patient awareness Illness perceptions, Medication and treatment adherence 16 20 Aboumatar, H. J et al [ 66 ] 2013 J Gen Intern Med Online and offline sources of information and support Combining patient-oncologist intervention to improve communication in advanced cancer 41 primary care physicians and 275 of their patients +++ Primary care clinic USA Hypertension Patient education Demographic data, Patient awareness Appointment intake information 18 21 Albada, A. et al [ 29 ] 2015 Patient Educ Couns Electronic pre-office visit checklist To help reduce waiting times and duplication of work, improve patient pathways and decrease wasted visits 197 patients + Breast cancer clinic Norway Breast cancer Decision aid tools, Pre-assessment tools, Reminders Demographic data, Medical history, Family history, Reason for referral, Symptoms, Medication Patient-provider communication, Perceived involvement in care, Adherence to visit scheduling, Visit length 18 22 Bruce, J. et al [ 60 ] 2018 J Cancer Educ Online and offline sources of information and support To evaluate teen feedback on an asthma question intervention designed to motivate teens to be more engaged during visits and …”
Section: Resultsmentioning
confidence: 99%
“…The analysis showed that different types of pre-visit techniques have been employed by authors to facilitate office visits and patient care. All of these plans can be categorized into eight different categories, utilizing an electronic pre-office checklist with 12 studies (24.5%) [ 25 , 29 35 , 48 , 58 , 59 , 68 ], educating patients and support them before each visit in form of online and offline source of information with 12 studies (24.5%) [ 23 , 36 42 , 60 62 , 66 , 74 ], applying an EHR-linked care program with different checklists and assessment tools with nine studies (18.4%) [ 22 , 43 , 44 , 49 , 63 , 67 , 70 , 71 , 73 ], using paper-based checklists with nine studies (18.4%) [ 45 , 46 , 50 – 52 , 64 , 65 , 69 , 72 ], preparing and assess patient with the pre-visit phone-based intervention with two studies (4.1%) [ 24 , 53 ], using self-triage or self-assessment tools with two studies (4.1%) [ 54 , 55 ], using automatic reminders and sheets with one article (2%) [ 56 ], and using pre-clinic consultation by other health care team member with one article (2%) to prepare the patient for each visit [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of those patients declining study participation have been described in detail previously. 8 Of the 309 consented patients, 244 received the questionnaire and 227 completed at least three of the knowledge questions; most patients (94%) completed all five knowledge questions. These patients comprise our study cohort.…”
Section: Resultsmentioning
confidence: 99%
“…7 In our multi-disciplinary breast program, we successfully developed an implementation strategy that facilitates the routine delivery of a web-based decision aid directly to patients in the informational gap prior to the first surgical consultation. 8 Our pilot project demonstrated that this approach was feasible and highly acceptable to both patient and clinic stakeholders.…”
Section: Introductionmentioning
confidence: 91%